Adaptive Leadership Training for Generation Z in Facing the Era of Technological Disruption at Madrasah Aliyah Negeri 1 Situbondo: Pelatihan Kepemimpinan Adaptif Bagi Generasi Z dalam Menghadapi Era Disrupsi Teknologi di Madrasah Aliyah Negeri 1 Situbondo - Nur Faifatur R, M Kurma; Arifin, Samsul; Baidawi, M. Kholil; Rosi, Fathor (STAI Nurul Huda Kapongan Situbondo, 2025)
The era of technological disruption demands the emergence of young generations who are not only digitally skilled but also possess adaptive and character-based leadership. Generation Z, who grew up in a digital environment, holds great potential as agents of change; however, they also face challenges such as low social empathy, dependence on technology, and weak interpersonal communication skills. This Community Service Program (PKM) aims to develop adaptive leadership based on digital literacy and character strengthening among students of Madrasah Aliyah Negeri 1 Situbondo through a descriptive qualitative approach with a participatory model. The training was conducted through several stages, including training and workshops, simulations and group discussions, technology-based mini projects, as well as mentoring and evaluation. Data were collected through participatory observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing through source triangulation. The results showed significant improvements in leadership insight, communication skills, teamwork, and students’ confidence. Previously passive students became more active, adaptive, and wise in utilizing technology to support organizational activities. The program also had a positive impact on student organizations, making them more structured, innovative, and responsive to technological developments. Thus, adaptive leadership training based on digital literacy proved effective in shaping visionary, collaborative, and integrity-driven young leaders. In the future, the program is recommended to be expanded with additional materials on digital ethics, artificial intelligence, and continuous mentoring to ensure students can apply their leadership skills in both school and community contexts.